PENGEMBANGAN LEMBAR KERJA SISWA BERBASIS ETNOMATEMATIKA DALAM MEMBANGUN PEMAHAMAN KONSEP SISWA - Hasanah, Sri Indriati; Hafsi, Ainur Rofiq; Zayyadi, Moh (Jurnal Pendidikan Matematika dan IPA, 2019)
This study aims to describe the quality of teaching materials developed in the form of ethnomatematic Student Worksheets (LKS) in building understanding of students' initial concepts that are valid, practical and effective. This research is a development research that refers to the simplified Thiagarajan 4-D model into three stages including defining, designing, developing. The product produced is a Student Activity Sheet based on ethnomatematics in building understanding of concepts, lesson plans and Tests of Learning Outcomes so that learning objectives are achieved. The results of the study show that the Student Activity Sheet is ethnomatemically based in developing the initial concept of student understanding that has been developed to meet the criteria of valid, practical and effective.